2022
DOI: 10.3389/fnins.2021.785595
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Analysis of Schizophrenia Patients Using Topological Properties of Structural and Functional Brain Networks: A Multimodal Magnetic Resonance Imaging Study

Abstract: Interest in the application of machine learning (ML) techniques to multimodal magnetic resonance imaging (MRI) data for the diagnosis of schizophrenia (SZ) at the individual level is growing. However, a few studies have applied the features of structural and functional brain networks derived from multimodal MRI data to the discriminative analysis of SZ patients at different clinical stages. In this study, 205 normal controls (NCs), 61 first-episode drug-naive SZ (FESZ) patients, and 79 chronic SZ (CSZ) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 93 publications
(105 reference statements)
1
7
0
Order By: Relevance
“…The rs-fMRI images were preprocessed using SPM8 ( https://www.fil.ion.ucl.ac.uk/spm; Institute of Neurology, University College London) and Data Processing & Analysis for Brain Imaging (DPABI; Yan et al, 2016 ). The preprocessing steps of sMRI images and rs-fMRI images were the same as those in our previous studies ( Wu et al, 2018 ; Kong et al, 2021 ; Huang et al, 2022 ; Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The rs-fMRI images were preprocessed using SPM8 ( https://www.fil.ion.ucl.ac.uk/spm; Institute of Neurology, University College London) and Data Processing & Analysis for Brain Imaging (DPABI; Yan et al, 2016 ). The preprocessing steps of sMRI images and rs-fMRI images were the same as those in our previous studies ( Wu et al, 2018 ; Kong et al, 2021 ; Huang et al, 2022 ; Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Three sMRI measurements, including GMV, WMV and structural degree centrality (sDC), and three fMRI measurements, including ReHo, ALFF and functional degree centrality (fDC), were calculated in each ROI of the AAL and BNA atlases. The calculation methods of the ROI features used in this study were the same as those in our previous studies ( Wu et al, 2018 ; Zang et al, 2021 ; Huang et al, 2022 ; Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its capability to deal with high-dimensional data, it has also been applied to classify between recent-onset depression and recent-onset psychosis using both neuroanatomical information and clinical data ( 51 ), to find neurocognitive subtypes based on cognitive performance and neurocognitive alterations in recent onset psychosis ( 52 , 53 ), to identify schizophrenia patients based on subcortical regions ( 54 ) or functional network connectivity data ( 55 ). A multimodal approach combining structural MRI, diffusion tensor imaging, and resting-state functional MRI data was tested to classify patients with chronic schizophrenia vs. patients with FEP comparing different algorithms such as Random Forest (RF), LR, Linear Discriminant Analysis (LDA), and K-Nearest Neighbor classification (KNN), and SVM, resulting in the latter as the best performing one ( 56 ). Steardo et al in a recent systematic review, analyzed 22 studies using SVM on fMRI as biomarkers to classify between schizophrenia patients and controls, where 19 studies reported a promising >70% accuracy ( 57 ).…”
Section: Common Machine Learning Algorithmsmentioning
confidence: 99%